Penina uliuli : contemporary challenges in mental health for Pacific peoples - Culbertson, Philip Leroy, 1944-; Agee, Margaret Nelson; Makasiale, Cabrini'Ofa (University of Hawaii Press, 2007)
This diverse collection of essays examines important issues related to mental health among Pacific Islanders through the topics of identity, spirituality, the unconscious, mental trauma, and healing. Contributors: Emeline Afeaki-Mafile'o, Margaret Nelson Agee, Siautu Alefaio, A. Aukahi Austin, Tina Berking, Philip Culbertson, Caroline Salumalo Fatialofa, Yvette Guttenbeil-Po'uhila, Joseph Keawe'aimoku Kaholokula, David Lui, Karen Lupe, Maika Lutui, Cabrini 'Ofa Makasiale, Tavita T. Maliko, Peta Pila Palalagi, Suiamai Simi, Seilosa Skipps-Patterson, Karanina Siaosi Sumeo, To'oa Jemaima Tiatia, Sione Tu'itahi, Fia T. Turner-Tupou.